A Memória da Matéria: Proposta de Intervenção na Quinta das Lages - Joana Dias Bandeira de Aguiar (2024)
This dissertation is motivated by a personal concern about the abandonment of Quinta das Lages, which, despite its historical and architectural value, has fallen into oblivion. It is proposed, then, to reflect on how to intervene in the ruins of the property, transforming it into a space to welcome visitors and adapting it to current needs. The work explores the relationship between the place and the subject matter, which from this investigation finds themes for the project. The questions and hesitations provided by the confrontation between the architect, the place and the matter that exists in it, built the project based on theoretical research that fuelled the design process. Throughout the process, questions emerged about the place, the buildings and the owners, going beyond the objective of finding a solution for Quinta das Lages. In this sense, the design process oscillates between reading the specificity of the place and its social and historical context, while exploring the way of thinking and intervening in the preexistence. In this work, the paths and directions of the project are recorded in order to find a possible solution for Quinta das Lages. Elements are collected that make it possible to recognise and value a dormant territory waiting for an intervention that is sensitive to the memory of the place.